The Small Tellurium Compound AS101 Ameliorates Rat Crescentic Glomerulonephritis: Association with Inhibition of Macrophage Caspase-1 Activity via Very Late Antigen-4 Inactivation - Hachmo, Yafit; Kalechman, Yona; Skornick, Itai; Gafter, Uzi; Caspi, Rachel R.; Sredni, Benjamin (Frontiers in Immunology, 2017)
Crescentic glomerulonephritis (CGN) is the most aggressive form of GN and, if untreated, patients can progress to end-stage renal failure within weeks of presentation. The α4β1 integrin (VLA-4) is an adhesion molecule of fundamental importance to the recruitment of leucocytes in inflammation. We addressed the role of VLA-4 in mediating progressive renal injury in a rat model of CGN using a small tellurium compound. AS101 [ammonium trichloro(dioxoethylene-o,o')tellurate]. This compound has been previously shown to uniquely inhibit VLA-4 activity by redox inactivation of adjacent thiols in the exofacial domain of VLA-4. The study shows that administration of AS101 either before or after Glomerular-basement-membrane anti serum injection, ameliorates crescent formation or preserves renal function. This was associated with profound inhibition of critical inflammatory mediators, accompanied by decreased glomerular infiltration of macrophages. Mechanistic studies demonstrated vla-4 inactivation on glomerular macrophages both in vitro and in vivo as well as inhibition of caspase-1 activity. Importantly, this cysteine protease activity modification was dependent on VLA-4 inactivation and was associated with the anti-inflammatory activity of AS101. We propose that inactivation of macrophage VLA-4 by AS101 in vivo results in a decrease of inflammatory cytokines and chemokines produced in the glomeruli of diseased rats, resulting in decreased further macrophage recruitment and decreased extracellular matrix expansion. Thus, AS101, which is currently in clinical trials for other indications, might be beneficial for treatment of CGN.